(untitled) (NAU Journal of Library and Information Science, 2024)
This study examined the influence of attitude towards use of e-resources and proficiency in information and communication technology skills on postgraduate law students‟ use of electronic information resources in two universities in Nigeria. The study adopted the survey research design. A questionnaire was used for data collection. The sample size for the study is 200 postgraduate law students. The data collected were critically analyzed using descriptive and inferential statistics. The overall mean score of 2.42 which is below the criterion mean 3.5 revealed that the frequency of e-resources use by postgraduate law students was very low. The self-reported level of proficiency in Information and Communication Technology skills was high (overall mean 2.89>criterion mean 2.5) and their attitude towards use of electronic information resources was positive (overall mean 2.70 >criterion mean 2.5). The study further showed that attitude towards e-resources use is not a significant predictor of e-resources use, but proficiency in information and communication technology skills has a significant relative effect on use of eresources. The study recommends that university libraries should provide access to e-resources via remote authentication system. This would enable postgraduate law students to access the library‟s e-resources 24/7 without any physical restriction. Links to electronic information resources should be provided through online public access catalogue and library dedicated website. The law librarian should partner with faculty of law members to create awareness of the benefits of electronic information resources use among postgraduate law students. The university libraries should also organize training for postgraduate law students to enable them acquire relevant information and communication technology skills required for information retrieval.